Aizuchi dalam Anime Movie Suzume no Tojimari Karya Makoto Shinkai - Febri Ali Fandani; Prisyanti Suciaty (Omiyage : Jurnal Bahasa dan Pembelajaran Bahasa Jepang, 2026)
Learning aizuchi is important because mistakes in its use can lead to misunderstandings and reduce the effectiveness of communication. This research focuses on the use of forms and functions of aizuchi found in the anime movie Suzume no Tojimari. The research uses a qualitative approach with a descriptive analysis method because the data examined are in the form of words that will be described and explained. After data collection and analysis, it was found 143 data divided into 126 instances of expression forms, 14 instances of repetition forms, 1 instance of paraphrase form, and 2 instances of other forms. Regarding the functions, there were 33 instances of listening signals, 35 instances of understanding signals, 10 instances of agreement signals, 12 instances of denial signals, and 53 instances of emotional expression signals. In this study, the most frequently occurring form of aizuchi is the expression form, while the most frequently occurring function of aizuchi is the emotional expression signal.